Preparation of Kayathirumeni Thylam: A Medicated Oil Used in Varma Medicine (International Journal of Food and Nutritional Sciences, 2022)
Varma is one of the traditional system of medicine in Kanyakumari District. Kayathirumeni Thylam is the oldest and most successful formula in Varma Medicine, and it heal general injuries and pain. The traditional practitioner’s special formula of Kayathirumeni is containing 16 plant extracts, 15 powered form of raw drugs, coconut oil and total ingredients are 33 in number. The main ingredient is leaf extract. Kayathirumeni Thylam used to cure cough, headache, hiccup, trauma, hematoma, sprain and joint diseases. The Kayathirumeni Thylam has good collection of properties and in action wise it can used internally and externally. In finally conclude that Kanyakumari district people used this Thylam as a very essential medical hit in their home.